GEOCHEMISTRY OF THE RHYOLITIC MAGMAS FROM THE STRELTSOVKA CALDERA (TRANSBAIKALIA, RUSSIA): A MELT INCLUSION STUDY - Chabiron A.; Cuney M.; Poty B.; Alyoshin A.P.; Golubev V.N.; Velitchkin V.I.; Deloule E. (My University, 2001)
The Streltsovka caldera located in Transbaikalia near the Chinese–Mongolian border represents the largest uranium field associated with volcanics in the world. All the rocks, volcanics and underlying granites, are deeply altered by hydrothermal fluids and their original major and trace element chemistry was strongly modified, particularly their primary mobile element concentrations such as fluorine, alkalis, uranium. To determine the primary geochemical characteristics of the magma associated with this giant ore field, a study of melt inclusions has been undertaken on the rhyolites. Many of the melt inclusions are well preserved in quartz phenocrysts from strongly altered rhyolites of the caldera. Si, Al, Fe, Na, K, Ca, F, Cl, Mn, Ti, P, S and Mg were analyzed by electron microprobe, U by fission tracks and H, U, Th, La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Er, Yb, Lu, Sc, Ti, V, Sr, Y, Nb, Ba, Hf by ion microprobe. The presence in melt inclusions, of daughter minerals such as fluorite, F-rich mica and REE fluocarbonate, and the composition of the silicate melt after homogenization, indicate that the Streltsovka rhyolites correspond to highly fractionated mildly peralkaline melts (1.04<Na+K/Al<1.10) whereas whole rock analyses indicate a peraluminous composition. The Streltsovka rhyolitic melts are rich in F (from 1.4 to 2.7 wt.%), and in U (14 to 23 ppm). They are relatively dry with a water content inferior to 2.4% H2O. The low Cl contents (0.2% Cl) in melt inclusions of the present study may be related to the mildly peralkaline character of the Streltsovka melts (NK/Al: 1.04 to 1.10). These melts are rich in REE and present moderate LREE fractionation, low HREE fractionation and a strongly negative Eu anomaly. The similar REE contents of Tulukuevskoe melt inclusions and whole rock indicate that there was no significant fractionation after trapping of the magma. On the other hand, the glasses from Krasny Kamen and Streltsovskoe rhyolites are richer in HREE than the whole rock. This agrees with an REE saturation of the magma at the trapping time that is confirmed by the crystallization of parisite as a daughter mineral in melt inclusions. Melt temperatures obtained from homogenization of the inclusions are relatively high for such magma (1015±30°C) and may be overestimated because of a possible volatile loss since the rhyolite formation. The lower Th (1000±20°C) obtained in Tulukuevskoe inclusions agrees with their higher F content (2.2% to 3.2%). The higher homogenization temperature of Krasny Kamen inclusions also agrees with the lower F content (0.6% to 0.8%).
Keywords: Transbaikalia; Streltsovka caldera; Uranium; Melt inclusions